Plasticity of Bi2Te3-family thermoelectric crystals - Ze Li; Tingting Deng; Pengfei Qiu; Chen Ming; Zhiqiang Gao; Lidong Chen; Xun Shi (Nature Communications)
Abstract The exceptional plasticity discovered most recently in defective Bi2Te3 bulk crystal inspires the great interest on investigating the plasticity of other Bi2Te3-family bulk crystals. In this work, Bi2Se3, Sb2Te3, and their solid solutions with Bi2Te3 are grown by the temperature gradient method to comprehensively clarify the relationship among chemical composition, native defect, microstructure, and plasticity of Bi2Te3-family compounds. Compared with Bi2Te3 bulk crystal, Bi2Se3 and Sb2Te3 bulk crystals exhibit poorer plasticity at room temperature. The origin is attributed to the lack of substantial antisite defects in Bi2Se3 and Sb2Te3 alike that in Bi2Te3, which impedes the formation of the high-density, diverse microstructures. Alloying either Se or Sb in Bi2Te3 modifies the native defects and microstructures and thus changes plasticity and thermoelectric performance. Finally, the composition range for the Bi2(Te,Se)3 and (Bi,Sb)2Te3 bulk crystals that simultaneously possess exceptional plasticity (maximum bending strain >10%) and thermoelectric performance is determined.